Integrated network pharmacology analysis, molecular docking, LC-MS analysis and bioassays revealed the potential active ingredients and underlying mechanism of Scutellariae radix for COVID-19 - Liu, Jiazheng; Meng, Jieru; Li, Runfeng; Jiang, Haiming; Fu, Lu; Xu, Ting; Zhu, Guo-Yuan; Zhang, Wei; Gao, Jin; Jiang, Zhi-Hong; Yang, Zi-Feng; Bai, Li-Ping (Frontiers in Plant Science, 2022)
Scutellariae Radix (“Huang-Qin” in Chinese) is a well-known traditional herbal medicine and popular dietary supplement in the world, extensively used in prescriptions of TCMs as adjuvant treatments for coronavirus pneumonia 2019 (COVID-19) patients in China. According to the differences in its appearance, Scutellariae Radix can be classified into two kinds: ZiQin (1~3 year-old Scutellariae Radix with hard roots) and KuQin(more than 3 year-old Scutellariae Radix with withered pithy roots). In accordance with the clinical theory of TCM, KuQin is superior to ZiQin in cooling down the heat in the lung. However, the potential active ingredients and underlying mechanisms of Scutellariae Radix for the treatment of COVID-19 remain largely unexplored. It is still not clear whether there is a difference in the curative effect of ZiQin and KuQin for the treatment of COVID-19. In this research, network pharmacology, LC-MS based plant metabolomics, and in vitro bioassays were integrated to explore both the potential active components and mechanism of Scutellariae Radix for the treatment of COVID-19. As the results, network pharmacology combined with molecular docking analysis indicated that Scutellariae Radix primarily regulates the MAPK and NF-κB signaling pathways via active components such as baicalein and scutellarin, and blocks SARS-CoV-2 spike binding to huamn ACE2 receptors. In vitro bioassays showed that baicalein and scutellarein exhibited more potent anti-inflammatory and anti-infectious effects than baicalin, the component with the highest content in Scutellariae Radix. Moreover, baicalein inhibited SARS-CoV-2’s entry into Vero E6 cells with an IC50 value of 142.50 µM in a plaque formation assay. Taken together, baicalein was considered to be the most crucial active component of Scutellariae Radix for the treatment of COVID-19 by integrative analysis. In addition, our bioassay study revealed that KuQin outperforms ZiQin in the treatment of COVID-19. Meanwhile, plant metabolomics revealed that baicalein was the compound with the most significant increase in KuQin compared to ZiQin, implying the primary reason for the superiority of KuQin over ZiQin in the treatment of COVID-19.